THE QUALITY ASSESMENT OF THE SAFETY ASPECTS OF SALTED FISH (Hemirampus brasiliensi ) IN THE TRADITIONAL MARKET AT PEKANBARU CITY - Ningsih, Endang Sulistya; Mus, Sukirno; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research purposes to determined the food safety aspects related to thesalted fish of Julung-julung (Hemirampus brasiliensi ) that use illegal preservativessold in the traditional market Pekanbaru. The method that used in this research was asurvey method which took sample from the population by involving interviews as adata collection tool. While fish samples were taken by using purposive samplingtechnique as much as 18 samples were selected from three traditional markets in thecity of Pekanbaru. Parameters t hat has been used in order to see of the illegalpreservation were chemical test and microbiological test (TPC). The results of thisresearch showed that there were three samples of salted fish Julung -julung(Hemirampus brasiliens) positive contained formaldehyde were sampled with thecode of KC2, PB1 and PC2. The third sample produced pink to purplish color afterthe sample extract drops antilin test kit. The result of the color also indicated that thesample contains at least 2 ppm. Meanwhile all neg ative samples containing borax.Parameter for microbiological analysis showed that all samples are not more than themaximum threshold 1x105 colony/gam.Keywords : quality, food savety, Hemirampus brasiliensi